2015
DOI: 10.1007/s11695-014-1542-1
|View full text |Cite
|
Sign up to set email alerts
|

The Hundred Most Cited Articles in Bariatric Surgery

Abstract: ABCDDV/1132 W orldwide overweight affects approximately two billion people, and Brazil occupies the fifth position with approximately 52% of the population in overweight and obesity. This scenario has contributed to the quantitative increase of bariatric surgery in our country, which is surpassed only by the United States. In recent years there were also several specialized journals in obesity and bariatric surgery, with an increasing number of publications. Ahmad SS et al1., in 2015, reported the 100 most fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 26 publications
0
39
0
3
Order By: Relevance
“…Besides the well-known fact that in citation analysis there is often a high proportion (in the case of our study 39%) of articles originating from the United States due to citation and reviewer behavior as well as socioeconomic factors [4,5,14] , a high proportion of the articles originated from institutions of more than one country. This underlines the trend to international collaboration studies, which are associated with a higher level of evidence in this study.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Besides the well-known fact that in citation analysis there is often a high proportion (in the case of our study 39%) of articles originating from the United States due to citation and reviewer behavior as well as socioeconomic factors [4,5,14] , a high proportion of the articles originated from institutions of more than one country. This underlines the trend to international collaboration studies, which are associated with a higher level of evidence in this study.…”
Section: Discussionmentioning
confidence: 55%
“…Modern database, such as the Web of Science (Thomson Reuters, Philadelphia, Pa., USA), renders citation analysis as a tool of growing importance to identify high impact journals in different fields [4][5][6] . Therefore, the aim was to identify the 100 most cited articles in the field of visceral surgery, and to summarize the provided knowledge and evidence, focusing on those articles that influence and shape surgeon's daily decision making or have the potential to modify current therapeutic concepts.…”
mentioning
confidence: 99%
“…Laparoscopic Sleeve-forming gastrectomy (LSFG), the restriction part of DS, was so described by several authors in 2005. Baltasar LSFG [75], according to Ahmad [76] is the 61 st most cited article in all the bariatric literature. Angrisani [77] claims that the LSFG is today the most commonly performed operation in the world.…”
Section: Seco Founding Membersmentioning
confidence: 99%
“…Ahmed recently [8] reported that our work [6] of 2005 was the 61 most cited article in bariatric surgery.…”
Section: Introductionmentioning
confidence: 93%